Optimizing Gender Equality Messages on the Mubadalah.id Website - Ma'rifah, Iza; Fanshoby, Muhammad; Hermansah, Tantan (Kalijaga Journal of Communication, 2024)
This qualitative study aims to measure the optimization of Search Engine Optimization (SEO) on content containing gender equality values ​​on the mubadalah.id website. This research focuses on the editorial team's and writers' efforts to use SEO on the mubadalah.id website using Computer-Mediated Communication (CMC) theory to optimize asynchronous communication. The values ​​of gender equality are seen from the perspective of Qira'ah Mubadalah, which has three indicators, namely a perspective (minzhar) that humanizes humans, a way of reading (qira'ah) reference texts by placing men and women as subjects and whole human beings, and ways of grouping (qa'idah) experiences, mutuality, or cooperation between men and women. This research uses interview and digital observation methods. The results show that mubadalah.id has a comprehensive SEO strategy, but there is still room for improvement in its implementation.